Fcγ Receptor IIB Controls Skin Inflammation in an Active Model of Epidermolysis Bullosa Acquisita - Kovacs, Balint; Tillmann, Jenny; Freund, Lisa-Christin; Nimmerjahn, Falk; Sadik, Christian D.; Bieber, Katja; Ludwig, Ralf J.; Karsten, Christian M.; Köhl, Jörg (Frontiers in Immunology, 2020)
Epidermolysis bullosa acquisita (EBA) is an autoimmune skin blistering disease characterized by IgG autoantibodies (aAb) against type VII collagen (COL7). The mechanisms controlling the formation of such aAbs and their effector functions in the skin tissue are incompletely understood. Here, we assessed whether the inhibitory IgG Fc receptor, FcyRIIB, controls the development of autoimmune skin blistering disease in an active model of EBA. For this purpose, we immunized congenic EBA-susceptible B6.SJL-H2s (B6.s) and B6.s-Fcgr2b-/- mice with the immunodominant vWFA2 region of COL7. B6.s-Fcgr2b-/- mice developed a strong clinical phenotype with 15% 3,3% of affected body surface area at week 4. In contrast, the body surface area in B6.s mice was affected to a maximum of 5% at week 6 with almost no disease signs at week 4. Surprisingly, we already found strong but similar COL7-specific serum IgG1 and IgG2b aAb production at week 2. Further, aAb and C3b deposition in the skin of B6.s and B6.s-Fcgr2b-/- mice increased between weeks 2-6 after vWFA2 immunization. Importantly, neutrophil skin infiltration and activation was much stronger in B6s-Fcgr2b-/- than in B6.s mice and already present at week 2. Also, the early aAb response in B6.s-Fcgr2b-/- mice was more diverse than in wt B6.s mice. Reactive oxygen species (ROS) release from infiltrating neutrophils play a crucial role as mediator of skin inflammation in EBA. In line, sera from B6.s and B6.s-Fcgr2b-/- mice induced strong ROS release from BM-neutrophils in vitro. In contrast to the antibody-transfer-induced EBA model, individual targeting of FcyRIII or FcyRIV decreased ROS release to 50%. Combined FcyR blocking abrogated ROS release from BM neutrophils. Also, ROS release induced by COL7-specific serum IgG aAbs was significantly higher using BM neutrophils from B6.s-Fcgr2b-/- than from B6.s mice. Together, our findings identified FcyRIIB as a suppressor of skin inflammation in the active EBA model through inhibition of early epitope spreading, protection from strong early neutrophil infiltration to and activation of neutrophils in the skin and suppression of FcyRIII activation by IgG1 aAbs which drive strong ROS release from neutrophils leading to tissue destruction at the dermal-epidermal junction.